Association of Experimental Chronic Arthritis with the Persistence of Group A Streptococcal Cell Walls in the Articular Tissue - Schwab, John H. (1967)
A single injection of isolated fragments of group A streptococcal cell walls into the joints of rabbits stimulated an initial acute reaction which was followed by a prolonged inflammatory process. The chronic process was characterized by hyperplasia of the synovial cells, diffuse infiltration of the villi by macrophages, and focal collections of lymphocytes in the stroma of the villi. These histological changes were similar to those seen in the early stages of rheumatoid arthritis. Antibodies specific for the mucopeptide and group-specific C polysaccharide antigens of group A streptococcal cell walls were labeled with either fluorescein or (125)I, and were used to demonstrate antigen in the synovial tissues. The antigens persisted within macro-phages for at least 5 weeks. Their presence correlated with the evolution of the chronic inflammatory process.